Selfhood, identity and madness in the works of Milan Kundera and Peter Carey - Graven, Ashley Holm (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2016)
Despite all the critical attention Milan Kundera's and Peter Carey's fiction has received, relatively little has been said about the way in which these authors problematise selfhood. In this study, I argue that these two writers share a preoccupation with the strictures placed on the individual by his/her location in language and discourse. I show that they deconstruct subjectivity with a view to intimating the possibility of momentarily transcending discursive control, and thereby inhabiting authentic selfhood. In addition, I demonstrate that both authors draw attention to the nature of language through their thematisation of madness, and I then trace the implications of this nexus between language and madness for the reader, who of course is a subject in language. My contention in this regard is that Carey and Kundera seek to instil in the reader a self-reflexive awareness of the ways in which his/her location in language shapes his/her perception of others. In turn, this awareness charges the reader with the responsibility of questioning his/her judgements, and thereby enables him/her to negotiate a measure of authenticity from his/her position in language.
Keywords: Uncatalogued